Efeito das práticas ESG no desempenho financeiro com moderação da restrição financeira nos países do BRICS - Vargas, Maiele Bastos de (2025)
Environmental, Social, and Governance (ESG) practices have become increasingly relevant in corporate management and investment decision-making. However, the relationship between ESG and financial performance remains a topic of debate in the literature, particularly in companies from emerging markets, where financial constraints may influence firms' ability to implement sustainable initiatives. Given this context, this study investigates the moderation of financial constraint (RF) in the relationship with ESG practices in the financial performance of companies from BRICS countries (Brazil, Russia, India, China, and South Africa). To achieve this objective, fixed-effects regression models were estimated, using return on assets (ROA) and Tobin’s Q (QT) as proxies for financial performance. As measures of financial constraint, the KZ (Kaplan Zingales), WW (Whited-Wu), and SA (Size-Age Index) indices were adopted. In addition to analyzing aggregate ESG, its three individual pillars—Environmental (E), Social (S), and Governance (G)—were examined separately, allowing for a more detailed investigation of each ESG dimension's effects. The results indicate that ESG has a positive and significant impact on firms' operational profitability (ROA), but its effect on market valuation (QT) is less evident and, in some cases, negative. This finding suggests that while ESG practices can drive efficiency and innovation, the market may not immediately recognize their financial benefits. Moreover, companies facing greater financial constraints tend to exhibit lower operational profitability, reinforcing the hypothesis that difficulties in accessing financing may limit firms' ability to achieve direct gains from ESG initiatives. The moderation analysis reveals that for highly constrained firms, the positive impact of ESG may be reduced, especially when resources for sustainable investments are limited. When analyzing results by country, the impact of ESG and financial constraints varied according to the economic and regulatory context of each BRICS nation. India and China showed the strongest effects of ESG on financial performance, while Brazil and Russia had moderate positive impacts. In South Africa, ESG exhibited a greater influence on market valuation, suggesting that South African investors may better recognize the benefits of sustainable practices. The findings of this study highlight the need to consider financial constraints as a key factor in determining the effectiveness of ESG practices, especially in emerging markets. Additionally, the results suggest that the impact of ESG on market value may depend on the time horizon required for these investments to generate perceptible returns. Thus, this research contributes to the literature by providing empirical evidence on the role of financial constraints in the relationship between ESG and financial performance, offering valuable implications for corporate managers, policymakers, and investors seeking to assess the true impact of ESG practices in the corporate landscape